Papyrus Oxyrhynchus 2359, 3876, 2619, 2803 - Stesichorus. (Mnemosyne, Supplements, 2003)
The work of Stesichoros, an ancient Greek poet of the early sixth century B.C., is transmitted in fragments only. This volume contains a new edition of some of the most interesting Stesichoros-papyri from the Oxyrhynchus collection. The papyri are analysed under various aspects: survey of relevant secondary literature, introduction about identification and contents of each papyrus (including archaeological evidence), papyrological description, metrics; the edition is complete with a Latin critical apparatus, translation and detailed commentary. A brief general introduction illustrates notorious problems concerning the author, the genre et cetera A bibliography and indices are provided at the end of the volume. The book will be welcomed by classicists and papyrologists alike.